Evidence for an iterative module in chain elongation on the azalomycin polyketide synthase - Hong, Hui; Sun, Yuhui; Zhou, Yongjun; Stephens, Emily; Samborskyy, Markiyan; Leadlay, Peter F. (Beilstein Journal of Organic Chemistry, 2016)
The assembly-line synthases that produce bacterial polyketide natural products follow a modular paradigm in which each round of chain extension is catalysed by a different set or module of enzymes. Examples of deviation from this paradigm, in which a module catalyses either multiple extensions or none are of interest from both a mechanistic and an evolutionary viewpoint. We present evidence that in the biosynthesis of the 36-membered macrocyclic aminopolyol lactones (marginolactones) azalomycin and kanchanamycin, isolated respectively from Streptomyces malaysiensis DSM4137 and Streptomyces olivaceus Tü4018, the first extension module catalyses both the first and second cycles of polyketide chain extension. To confirm the integrity of the azl gene cluster, it was cloned intact on a bacterial artificial chromosome and transplanted into the heterologous host strain Streptomyces lividans, which does not possess the genes for marginolactone production. When furnished with 4-guanidinobutyramide, a specific precursor of the azalomycin starter unit, the recombinant S. lividans produced azalomycin, showing that the polyketide synthase genes in the sequenced cluster are sufficient to accomplish formation of the full-length polyketide chain. This provides strong support for module iteration in the azalomycin and kanchanamycin biosynthetic pathways. In contrast, re-sequencing of the gene cluster for biosynthesis of the polyketide β-lactone ebelactone in Streptomyces aburaviensis has shown that, contrary to a recently-published proposal, the ebelactone polyketide synthase faithfully follows the colinear modular paradigm.
Keywords: colinearity; ebelactone; enzyme catalysis; marginolactone; natural products; polyketide synthase

(untitled) - Staunton, J.; Weissman, K. J. (Nat. Prod. Rep., 2001)

(untitled) - Fischbach, M. A.; Walsh, C. T. (Chem. Rev., 2006)

(untitled) - Smith, S.; Tsai, S.-C. (Nat. Prod. Rep., 2007)

(untitled) - Hertweck, C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Jenke-Kodama, H.; Sandmann, A.; Müller, R.; Dittmann, E. (Mol. Biol. Evol., 2005)

(untitled) - Weissman, K. J.; Leadlay, P. F. (Nat. Rev. Microbiol., 2005)

(untitled) - Wilkinson, B.; Kendrew, S. G.; Sheridan, R. M.; Leadlay, P. F. (Expert Opin. Ther. Pat., 2003)

(untitled) - Challis, G. L. (J. Med. Chem., 2008)

(untitled) - Katz, L.; Baltz, R. H. (J. Ind. Microbiol. Biotechnol., 2016)

(untitled) - Moss, S. J.; Martin, C. J.; Wilkinson, B. (Nat. Prod. Rep., 2004)

(untitled) - Fisch, K. M. (RSC Adv., 2013)

(untitled) - Chen, H.; Du, L. (Appl. Microbiol. Biotechnol., 2016)

(untitled) - Nguyen, T.; Ishida, K.; Jenke-Kodama, H.; Dittmann, E.; Gurgui, C.; Hochmuth, T.; Taudien, S.; Platzer, M.; Hertweck, C.; Piel, J. (Nat. Biotechnol., 2008)

Poster abstract A70 - Rudd, B. A. M.; Noble, D.; Foster, G.; Lane, S. J.; Webb, G. (Abstracts of the Sixth International Symposium on Genetics of Industrial Microorganisms (GIM 90) (ISBN 2087805-004-5), 12.8.1990-18.8.1990)

(untitled) - Wilkinson, B.; Foster, G.; Rudd, B. A. M.; Taylor, N. L.; Blackaby, A. P.; Sidebottom, P. J.; Cooper, D. J.; Dawson, M. J.; Buss, A. D.; Gaisser, S.; Böhm, I. U.; Rowe, C. J.; et al. (Cell Chem. Biol., 2000)

(untitled) - Hardt, I. H.; Steinmetz, H.; Gerth, K.; Sasse, F.; Reichenbach, H.; Höfle, G. (J. Nat. Prod., 2001)

(untitled) - Rowe, C. J.; Böhm, I. U.; Thomas, I. P.; Wilkinson, B.; Rudd, B. A. M.; Foster, G.; Blackaby, A. P.; Sidebottom, P. J.; Roddis, Y.; Buss, A. D.; Staunton, J.; Leadlay, P. F. (Cell Chem. Biol., 2001)

(untitled) - Thomas, I.; Martin, C. J.; Wilkinson, C. J.; Staunton, J.; Leadlay, P. F. (Cell Chem. Biol., 2002)

(untitled) - Beck, B. J.; Yoon, Y. J.; Reynolds, K. A.; Sherman, D. H. (Cell Chem. Biol., 2002)

(untitled) - Gaitatzis, N.; Silakowski, B.; Kunze, B.; Nordsiek, G.; Blöcker, H.; Höfle, G.; Müller, R. (J. Biol. Chem., 2002)

(untitled) - He, J.; Hertweck, C. (Cell Chem. Biol., 2003)

(untitled) - He, J.; Hertweck, C. (ChemBioChem, 2005)

(untitled) - Olano, C.; Wilkinson, B.; Moss, S. J.; Braña, A. F.; Méndez, C.; Leadlay, P. F.; Salas, J. A. (Chem. Commun., 2003)

(untitled) - Olano, C.; Wilkinson, B.; Sánchez, C.; Moss, S. J.; Sheridan, R.; Math, V.; Weston, A. J.; Braña, A. F.; Martin, C. J.; Oliynyk, M.; Méndez, C.; Leadlay, P. F.; et al. (Cell Chem. Biol., 2004)

(untitled) - Tatsuno, A.; Arakawa, K.; Kinashi, H. (J. Antibiot., 2007)

(untitled) - Dickschat, J. S.; Vergnolle, O.; Hong, H.; Garner, S.; Bidgood, S. R.; Dooley, H. C.; Deng, Z.; Leadlay, P. F.; Sun, Y. (ChemBioChem, 2011)

(untitled) - Busch, B.; Ueberschaar, N.; Behnken, S.; Sugimoto, Y.; Werneburg, M.; Traitcheva, N.; He, J.; Hertweck, C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Menche, D.; Arikan, F.; Perlova, O.; Horstmann, N.; Ahlbrecht, W.; Wenzel, S. C.; Jansen, R.; Irschik, H.; Müller, R. (J. Am. Chem. Soc., 2008)

(untitled) - Müller, S.; Rachid, S.; Hoffmann, T.; Surup, F.; Volz, C.; Zaburannyi, N.; Müller, R. (Chem. Biol., 2014)

(untitled) - Wyatt, M. A.; Ahilan, Y.; Argyropoulos, P.; Boddy, C. N.; Magarvey, N. A.; Harrison, P. H. M. (J. Antibiot., 2013)

(untitled) - Tang, X.; Li, J.; Millán-Aguiñaga, N.; Zhang, J. J.; O'Neill, E. C.; Ugalde, J. A.; Jensen, P. R.; Mantovani, S. M.; Moore, B. S. (ACS Chem. Biol., 2015)

(untitled) - Tao, W.; Yurkovich, M. E.; Wen, S.; Lebe, K. E.; Samborskyy, M.; Liu, Y.; Yang, A.; Liu, Y.; Ju, Y.; Deng, Z.; Tosin, M.; Sun, Y.; et al. (Chem. Sci., 2016)

(untitled) - Busch, B.; Ueberschaar, N.; Sugimoto, Y.; Hertweck, C. (J. Am. Chem. Soc., 2012)

(untitled) - Sugimoto, Y.; Ishida, K.; Traitcheva, N.; Busch, B.; Dahse, H.-M.; Hertweck, C. (Chem. Biol., 2015)

(untitled) - Hong, H.; Fill, T.; Leadlay, P. F. (Angew. Chem., Int. Ed., 2013)

(untitled) - Hong, H.; Samborskyy, M.; Lindner, F.; Leadlay, P. F. (Angew. Chem., Int. Ed., 2016)

(untitled) - Uotani, K.; Naganawa, H.; Aoyagi, T.; Umezawa, H. (J. Antibiot., 1982)

(untitled) - Bisang, C.; Long, P. F.; Cortés, J.; Westcott, J.; Crosby, J.; Matharu, A.-L.; Cox, R. J.; Simpson, T. J.; Staunton, J.; Leadlay, P. F. (Nature, 1999)

(untitled) - Caffrey, P. (Cell Chem. Biol., 2005)

(untitled) - Reid, R.; Piagentini, M.; Rodriguez, E.; Ashley, G.; Viswanathan, N.; Carney, J.; Santi, D. V.; Hutchinson, C. R.; McDaniel, R. (Biochemistry, 2003)

(untitled) - Keatinge-Clay, A. T. (Chem. Biol., 2007)

(untitled) - Kwan, D. H.; Sun, Y.; Schulz, F.; Hong, H.; Popovic, B.; Sim-Stark, J. C. C.; Haydock, S. F.; Leadlay, P. F. (Chem. Biol., 2008)

(untitled) - Del Vecchio, F.; Petkovic, H.; Kendrew, S. G.; Low, L.; Wilkinson, B.; Lill, R.; Cortés, J.; Rudd, B. A.; Staunton, J.; Leadlay, P. F. (J. Ind. Microbiol. Biotechnol., 2003)

(untitled) - Luhavaya, H.; Dias, M. V. B.; Williams, S. R.; Hong, H.; de Oliveira, L. G.; Leadlay, P. F. (Angew. Chem., Int. Ed., 2015)

(untitled) - Aparicio, J. F.; Molnár, I.; Schwecke, T.; König, A.; Haydock, S. F.; Khaw, L. E.; Staunton, J.; Leadlay, P. F. (Gene, 1996)

(untitled) - Yurkovich, M. E.; Tyrakis, P. A.; Hong, H.; Sun, Y.; Samborskyy, M.; Kamiya, K.; Leadlay, P. F. (ChemBioChem, 2012)

(untitled) - Zhou, Y.; Murphy, A. C.; Samborskyy, M.; Prediger, P.; Dias, L. C.; Leadlay, P. F. (Chem. Biol., 2015)

(untitled) - Paterson, I.; Hulme, A. N. (J. Org. Chem., 1995)

(untitled) - Tang, L.; Ward, S.; Chung, L.; Carney, J. R.; Li, Y.; Reid, R.; Katz, L. (J. Am. Chem. Soc., 2004)

(untitled) - Grabley, S.; Hammann, P.; Räther, W.; Wink, J.; Zeeck, A. (J. Antibiot., 1990)

(untitled) - Yuan, G.; Hong, K.; Lin, H.; She, Z.; Li, J. (Mar. Drugs, 2013)

(untitled) - Beyer, S.; Kunze, B.; Silakowski, B.; Müller, R. (Biochim. Biophys. Acta, 1999)

(untitled) - Silakowski, B.; Kunze, B.; Müller, R. (Gene, 2001)

(untitled) - Baltz, R. H. (J. Ind. Microbiol. Biotechnol., 2010)

(untitled) - Sosio, M.; Giusino, F.; Cappelano, C.; Bossi, E.; Puglia, A. M.; Donadio, S. (Nat. Biotechnol., 2000)

(untitled) - Gomez-Escribano, J. P.; Bibb, M. J. (J. Ind. Microbiol. Biotechnol., 2014)

(untitled) - Gregory, M. A.; Till, R.; Smith, M. C. M. (J. Bacteriol., 2003)

Practical Streptomyces Genetics - Kieser, T.; Bibb, M.; Buttner, M.; Chater, K.; Hopwood, D. (The John Innes Foundation, 2000)